2015
DOI: 10.1111/1756-185x.12805
|View full text |Cite
|
Sign up to set email alerts
|

Overlooked hematological markers of disease activity in rheumatoid arthritis

Abstract: We found that the MPV value may serve as a marker of the absence of acute-phase disease, and the NLR level as a marker of the presence of such disease, in patients with RA. More detailed analysis of disease activity is required to further explain the associations of the markers described above with disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
57
3
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 16 publications
7
57
3
4
Order By: Relevance
“…25,26 Kisacik et al 16 have shown that the MPV values in patients with ankylosing spondylitis and RA were significantly lower than controls and there was a significant negative correlation between the MPV value and the level of disease activity. The study of Tekeoglu et al 8 supports this study and found a negative correlation between MPV values and disease activity. Yazici et al 25 found that the MPV values in RA patients were positively correlated with both DAS28 and disease activity levels.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…25,26 Kisacik et al 16 have shown that the MPV values in patients with ankylosing spondylitis and RA were significantly lower than controls and there was a significant negative correlation between the MPV value and the level of disease activity. The study of Tekeoglu et al 8 supports this study and found a negative correlation between MPV values and disease activity. Yazici et al 25 found that the MPV values in RA patients were positively correlated with both DAS28 and disease activity levels.…”
Section: Discussionsupporting
confidence: 81%
“…22,23 NLR has been shown to be higher in RA group compared to control group and associated with disease activity in several publications. [8][9][10] We also found that NLR was higher in RA patients than the control group and a positive significant correlation was present with DAS28.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We support that vitamin B12-deficient patients have inflammatory conditions and MPV reflects the inflammatory position. Similarly, MPV was found to have a relationship with some inflammatory processes such as coronary ischemia, preeclampsia, ischemic stroke, rheumatoid arthritis, and inflammatory bowel disease [25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%